Characterization of WO3/ZnO nanocomposites synthesized by flame spray pyrolysis - C. Siriwong (2018)
Flame spray pyrolysis (FSP) was employed to synthesize pure ZnO and WO3/ZnO nanocomposites containing 0.25, 0.50, 0.75 and 1.0 mol% WO3. WO3is one of the most versatile and widely applied catalytic metal oxides. Precursor solutions of zinc naphthenate and tungsten ethoxide in ethanol were sprayed and combusted, resulting in crystalline and nanostructured particles. The crystalline phase, morphology and size of the nanoparticles were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The specific surface area of the nanocomposites was measured by nitrogen adsorption (BET analysis). The ZnO nanocomposites were observed as particles having clear spheroidal, hexagonal and rod-like morphologies. The crystallite sizes of spheroidal and hexagonal ZnO particles were in the range of 5-20 nm. ZnO nanorods were found to be range from 5-10 nm in width and 10-25 nm in length. The WO3compositions of the ZnO samples were verified by energy dispersive x-ray spectroscopy (EDS). © 2009 Amrican Institute of physics.